PS-003 Pharmaceutical interventions in the field of oncohaematology. (24th March 2015) - Manzaneque, A; Olivé, A; Mensa, M; Do Pazo-Oubiña, F; Creus, N; Codina, C
Abstract : Background: Pharmaceutical validation is considered an essential process in detecting medicines errors in chemotherapy. Purpose: To describe and analyse pharmaceutical interventions (PIs) carried out in oncohaematology patients during 2012–13. Material and methods: Retrospective observational study. Data were collected from the PI reporting platform, which comprised both hospitalised and outpatients. Information collected included: demographic data, inpatient or outpatient setting, drug, dosage, reason for PI, type of PI and acceptance. PIs were categorised in 12 groups (dosage adjustment; dosing schedule; drug; administration route; dosage form; frequency; dispensed; initiation and duration of treatment; treatment monitoring; suspension and others) and were associated with 52 different reasons for the intervention. Drugs involved were classified into chemotherapy (chemo), related or unrelated. PIs were analysed using Excel. Acceptance data was categorised as accepted or no information available. Results: 3, 294 PIs (1, 109 patients) were recorded (4.5 PI/day). In-patients accounted for nearly all PIs (95%) and 88% of drugs involved were unrelated to chemo. The main type of PI reported was others (38.5%). The most common reasons were: incorrect use of electronic prescribing program (21.2%), adapting dosage forms (17.9%), pharmaceutical care/patient information (14%). Change of dose (24.4%) and schedule adjustment (22.2%) were the most frequent types of PI within chemo-related drugs. Drugs related to higher notification rates were: trastuzumab (4.2%), gemcitabine/carboplatin (2.9%) and paclitaxel/erlotinib (2.0%) among chemo drugs, and antiemetic treatment (38.3%), calcium folinate (6.0%), filgrastim (6.0%) and zoledronic acid (4.9%) within the chemo-related drugs. PI global acceptance was 51%, but increased to 93% considering only chemo drugs. Conclusion: PIs were mainly recorded in the in-patient setting and focused on non-chemo drugs. The different acceptance rate between chemo and non-chemo drugs, explained by the lack of recorded acceptances, highlights the need for an improvement in the reporting tool. The results suggest the need for standardisation of the PI reporting and evaluation process. Reference: MJ Otero, et al . Farmacia Hospitalaria 27(3):137–49 No conflict of interest.